Textile antenna for first-person view goggles - André, Luís (2021)
Unmanned Aerial Vehicles, also known as drones, are vehicles controlled remotely. First-Person View (FPV) technology allows these vehicles to have greater versatility and be more easily piloted. The antennas currently used for video transmission are bulky and uncomfortable, so there is a need for this volume to be reduced to increase portability, being this the focus of the paper. The antenna was developed in textile materials to reduce its size and weight, as these materials allow for a better comfort and a reduced footprint. This paper presents a microstrip array adapted for the frequencies used in FPV video transmission. The designed textile antenna was compared with a commercially available rigid antenna used for this transmission. The comparison shows promising results for the antenna made of textile materials. The main goal of increasing the comfort and portability of the FPV goggles was achieved.